2006
DOI: 10.1002/hep.21507
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the applicability of noninvasive fibrosis markers in HIV/HCV co-infected patients

Abstract: We read with interest the article by Ikeda et al. 1 The authors have elegantly shown that flavustatin, atorvastatin, and simvastatin exert a strong inhibitory effect on HCV replication in their in vitro model. Such an effect was drastically increased when these statins were used in combination with interferon-alpha. The authors report that fluvastatin exhibited the strongest anti-HCV activity, whereas atorvastatin and simvastatin showed moderate inhibitory effects. Ikeda and colleagues argue that these statins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Using these cutoffs, liver biopsy could have been avoided in 71% of the patients. We have recently contributed to the external validation of the FIB‐4 model in HIV‐HCV co‐infected patients (31). In order to expand the applicability of this index, we proposed a modified model with AST and ALT levels expressed as times the ULN.…”
Section: Discussionmentioning
confidence: 99%
“…Using these cutoffs, liver biopsy could have been avoided in 71% of the patients. We have recently contributed to the external validation of the FIB‐4 model in HIV‐HCV co‐infected patients (31). In order to expand the applicability of this index, we proposed a modified model with AST and ALT levels expressed as times the ULN.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also showed a similar performance between FIB-4 and FibroTest ® [42] . Several other studies reported that the FIB-4 index had a variable degree of accuracy in HCVinfected subjects [43][44][45][46][47] . We performed a comparison between FIB-4 and APRI and found similar AUROCs for both models (0.811 vs 0.793) [23] .…”
Section: Serum Biomarkersmentioning
confidence: 96%
“…Le score FIB-4 a récemment été réévalué [12] et sa performance diagnostique apparaît similaire à l'étude princeps pour le diagnostic de la fibrose sévère F3-F4 chez les co-infectés VIH-VHC [13]. Elastomé trie impulsionnelle C'est une méthode physique qui, grâce à une petite impulsion, mesure l'élasticité du foie qui est proportionnelle au degré de la fibrose hépatique [14].…”
Section: Tests De Fibrose Au Cours Des Co-infections Vih/hépatites VIunclassified